Same storm, different boats! The impact of COVID-19 on the wellbeing of school communities. Issue 1 (30th August 2021) - O'Toole, Catriona; Simovska, Venka
Abstract : Purpose: The COVID-19 pandemic has impacted the functioning of education systems in a multitude of ways. In Ireland schools closed on March 12th and remained closed for the remainder of the academic year. During this time educators engaged with students, families and colleagues in new and diverse ways. The purpose of this study was to explore educators' experiences during the closures, particularly regarding the impact of the pandemic on the wellbeing of students, school staff and wider school communities. Design/methodology/approach: A series of one-to-one interviews, lasting approximately one hour, were conducted in July 2020 with 15 education professionals online via Zoom or Microsoft Teams. Participants occupied various roles (classroom teacher, school leader, special educational needs coordinator, etc.) and worked in a diverse range of communities in Ireland. Qualitative data from interviews were transcribed and emergent themes identified through an inductive followed by deductive analytic approach. Findings: The interviews highlighted the central role that schools play in supporting their local communities and the value teachers place on their relationships with students and families. Many teachers and school leaders found themselves grappling with new identities and professional boundaries as they worked to support, care for and connect with the students and families they serve. There was considerable concern expressed regarding the plight of vulnerable or marginalised students for whom the school ordinarily offered a place of safety and security. Originality/value: The findings reveal how COVID-19 has exacerbated pre-existing inequalities and the central role of schools in promoting the health and wellbeing of all its members.